Beneficial Effect of Sugar Osmolytes on the Refolding of Guanidine Hydrochloride-Denatured Trehalose-6-phosphate Hydrolase from Bacillus licheniformis. (13th January 2015) - Chen, Jiau-Hua; Chi, Meng-Chun; Lin, Min-Guan; Lin, Long-Liu; Wang, Tzu-Fan
Abstract : The influence of three sugar osmolytes on the refolding of guanidine hydrochloride- (GdnHCl-) denatured trehalose-6-phosphate hydrolase of Bacillus licheniformis ( Bl TreA) was studied by circular dichroism (CD) spectra, fluorescence emission spectra, and the recovery of enzymatic activity. These experimental results clearly indicated that sorbitol, sucrose, and trehalose at a concentration of 0.75 M improved the refolding yields of GdnHCl-denatured Bl TreA, probably due to the fact that these sugars favored the formation of tertiary architectures. Far-UV CD measurements demonstrated the ability of sugar osmolytes to shift the secondary structure of GdnHCl-denatured enzyme towards near-native conformations. ANS fluorescence intensity measurements revealed a reduction of exposed hydrophobic surfaces upon the treatment of denatured enzyme with sugar osmolytes. These observations suggest that sugar osmolytes possibly play a chaperone role in the refolding of chemically denatured Bl TreA.